EKSTRAKSI KARAGINAN RUMPUT LAUT MERAH (Kappaphycus alvarezii) DENGAN PERLAKUAN PERENDAMAN DALAM LARUTAN BASA - Panggabean, Jessica E; Dotulong, Verly; Montolalu, Roike Iwan; Damongilala, Lena Jeane; Harikedua, Silvana Dinaintang; Makapedua, Daisy Monica (Media Teknologi Hasil Perikanan, 2018)
Semi-refined carrageenan are a type of carrageeanan product that have a low level of purity because it still contains a small amount of selulose within the carageenan. The purpose of this study is to find out the effect of the concentration of both NaOH and KOH towards rendemen, and the physical and chemical charactheristic of semi refined carrageenan made from kappaphycus alvarezii seaweed,  and also to minimize the use of chemical product on SRC production process. The method used in this study is steaming method. The results are the rendemen from NaOH is 10% and KOH 14%. This proves that the concentration of alkali affects the amount of rendemen. The higher the amount of alkali used, the higher the amount of rendemen obtained.  Water content obtained from the NaOH samples are 3,75%; while those from the KOH samples are 5%.  The ash content of semi-refined carrageenan obtain from NaOH samples are 55,42% and KOH are 55,27%. For the pH level on semi-refined carrageenan obtain from the NaOH samples are 8,06; and KOH are 8,69. The alkali concentration  greatly affects the amount of rendemen that is obtained because a higher concentration of alkali during the alkalization process will result in higher pH level, therefore the extration ability of alkali are increased.